Modeling for extraction of oil from walnut and sesame using batch flow cold press oil extraction system. Issue 4 (22nd February 2022) - Ghiasi, Pedram; Sohrabi, Omid; Rahmati, Edris; Najafi, Gholamhassan; Mohamed, Mazlan; Ghasemnezhad, Azim
Abstract: In this study, a batch flow oil extraction system was used for extraction of oil from walnut ( Juglans regia L.) and Sesamum ( Indicum sesame ). Sample mass (g), applied pressure (MPa), and processing temperature of oil (°C) were selected as independent variables and oil extraction mass percentage and oil analysis as dependent variables. Response surface methodology was employed for conducting statistical analysis, modeling, and data optimization. The results revealed that the highest percentage of oil extraction for walnut was obtained at a pressure of 10.5 MPa, a temperature of 31.5°C, and a sample weight of 8 g, with a value of 25.36%. Also, the highest percentage of oil extraction for Sesamum was obtained at the pressure of 13.88 MPa, the temperature of 31.5°C, and a sample value of 20 g with a value of 22.4%. Optimal level of independent variables for walnut and sesame were 8.03 g, 10.41 MPa, and 27.37°C; 20 g, 13.88 MPa, and 27°C, respectively. In this optimum condition, the amount of sesame and walnut peroxide was 10 ± 0.03 and 1.9 ± 0.07 (meq O2/kg), respectively. Likewise, the amount of acid for sesame and walnut was 1.53 ± 0.05 and 0.06 ± 0.02 g/%, separately. Linoleic acid (42.7–51.15), oleic acid (38.6–24.03), palmitic acid (10.87–8.21), and stearic acid (5.5–3.39) were the most common fatty acid components in sesame and walnuts, respectively. Abstract : A new cold press oil extraction system was employed for extracting the oil from oilseeds (walnut and sesame) in the low volume. Sample mass (g), applied pressure (MPa), and processing temperature of oil (°C) were selected as independent variables. Response surface methodology was employed for statistical analysis and data optimization. Optimal level of independent variables for walnut and sesame were 8.03 g, 10.41 MPa, and 27.37°C; 20 g, 13.88 MPa, and 27°C, respectively.